2015
DOI: 10.1016/j.chb.2015.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Open educational resources repositories literature review – Towards a comprehensive quality approaches framework

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0
25

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(85 citation statements)
references
References 75 publications
2
58
0
25
Order By: Relevance
“…They concluded that many interactive visualizations do not appear to be well designed, either from a pedagogical nor from an interface design perspective. Studies have shown that quality assurance of the LORs is a significant factor when predicting the success of repositories (Clements et al 2015). Therefore, developers of LORs are responsible for providing quality assurance information to the users.…”
Section: Fig 6 An Example Of a Learning Object From Research Ideasmentioning
confidence: 99%
“…They concluded that many interactive visualizations do not appear to be well designed, either from a pedagogical nor from an interface design perspective. Studies have shown that quality assurance of the LORs is a significant factor when predicting the success of repositories (Clements et al 2015). Therefore, developers of LORs are responsible for providing quality assurance information to the users.…”
Section: Fig 6 An Example Of a Learning Object From Research Ideasmentioning
confidence: 99%
“…Repositories are built not only to collect and disseminate materials, but enable users to collaborate and review, comment on and rate the content they access (Atenas & Havemann, 2013). However, research indicates that (a) the most common behaviour on open repositories is non-generative use (Pynoo, Tondeur, van Braak, Duyck, Sijnave, & Duyck, 2012;Sabourin, Kosturko, & McQuiggan, 2014), and (b) the possibility of social interaction does not necessarily equate active participation in social interaction (Clements, Pawlowski, & Manouselis, 2015). In recent years, gamification, or the implementation of game features in non-game contexts, and social networking elements such as likes, reactions and scores have been hyped as a technique to channel user engagement, piquing the interest of academic communities beyond success in marketing contexts (Zourou & Lamy, 2013;Zourou, 2016): can the positive effects of game mechanics be transferred to educational settings?…”
mentioning
confidence: 99%
“…Besides elaborating on the concept of OERs, the focus of the latest research has started to shift to implementation-related issues such as models of OER lifecyles and processes (Downes, 2007;McGreal, 2010;Langen & Bitter-Rijkema, 2012;, programming aspects Green, Jones, Pearson, & Gkatzidou, 2006;Richter & Pawlowski, 2007) and the quality standards of OER repositories (Clements, Pawlowski, & Manouselis, 2015). Moreover, the impact of OERs on higher education and lifelong learning institutions (Das, 2011) has also been investigated.…”
Section: Oer and Related Conceptsmentioning
confidence: 99%
“…Some studies were dedicated to researching funding issues (Hylén, 2006), the development of business models (Langen & Bitter-Rijkema, 2012) and comparison to prior movements such as free and open software sources to avoid barriers and pitfalls (Vukovic & Martin, 2009). Technical frameworks were developed (Manisha & Bandyopadhyay, 2009), and further studies on the quality of repositories (Clements et al, 2015) and correct use of licenses (Hylén, 2006;Hylén & Schuller, 2007) were published. Despite these findings, authors have concluded that '…there will certainly be many more challenges ahead' (Atkins et al, 2007, p. 9).…”
Section: Oer Barriers and Related Conceptsmentioning
confidence: 99%